PP26 Incidence of acute respiratory failure cases in west midlands ambulance service (WMAS) – sub-study of ACUTE (ambulance CPAP: use, treatment effect and economics) trial. Issue 10 (24th September 2019) - Gunson, Imogen M; Herbert, Esther; Fuller, Gordon
Abstract : Background: Acute respiratory failure (ARF) is a life-threatening emergency and pre-hospital CPAP may improve outcomes. A CPAP cost-effectiveness determinant is the incidence of eligible patients with ARF. This sub-study of the ACUTE trial aimed to determine the number of adults with ARF potentially suitable for CPAP, presenting to WMAS. Methods: This observational study was conducted between 1 st August 2017 and 31 st July 2018. Adult patients presenting with SpO2 <94% were identified from WMAS electronic patient records. Electronic filters applied ACUTE trial inclusion and exclusion criteria, with subsequent manual clinical review by a research paramedic. A second research paramedic checked a sub-sample for inter-rater agreement. Overall and monthly incidence rates were calculated, census data provided the population denominator. Results: 108, 391 potential patients were identified from electronic patient records (EPR), after filter application 4, 526 cases were eligible for review (Figure 1). After review, 1017 cases were considered CPAP candidates. Inter-rater agreement was 86%. Overall incidence was 17.35 per 100, 000 population per year (95%CI 16.3–18.5). Marked seasonal variation was present, increasing over winter (Figure 2). Urban areas had the highest proportion of eligible patients (67.6% v 18.3% Rural v 14.2% semi-rural); and 53.0% of all eligible were male. Conclusions: The incidence of eligible ARF patients impacts on the cost-effectiveness of pre-hospital CPAP, but previous reports have been variable, using sub-optimal methods or from non-UK settings. We report a valid NHS estimate of 17 patients per 100, 000 who do not respond to current pre-hospital ARF management and could be candidates for CPAP.